Front Cover Image, Volume 117, Number 2, February 2020. Issue 2 (9th January 2020) - Duroy, Pierre‐Olivier; Bosshard, Sandra; Schmid‐Siegert, Emanuel; Neuenschwander, Samuel; Arib, Ghislaine; Lemercier, Philippe; Masternak, Jacqueline; Roesch, Lucien; Buron, Flavien; Girod, Pierre‐Alain; Xenarios, Ioannis; Mermod, Nicolas
Abstract : The cover image is based on the Original Article Characterization and mutagenesis of Chinese hamster ovary cells endogenous retroviruses to inactivate viral particle release by PIERRE‐OLIVIER DUROY et al., https://doi.org/10.1002/bit.27200 .